(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
The article presents an analysis of the results of clinical and laboratory studies. In children with cystic fibrosis, the main clinical symptoms from the bronchopulmonary system were: cough, shortness of breath, oral wheezing, lethargy and loss of appetite. Upon admission to the hospital, the general condition of the patients was most of all regarded as severe. The most common pathogens of exacerbation of the disease were S. aureus – 31 (26.0%) Pseudomonas aeruginosa - 24 (20.0%). Based on the results of the study, the frequency of mutations in the CFTR gene and their effect on the nature of the course were determined. The significant role of the 4 mutations of the CFTR-F508del, CFTR-2143delT, R709X, Y569D gene, which are most common in Uzbekistan, has been revealed.